Expansion of CD8+ T cell population in Lassa virus survivors with low T cell precursor frequency reveals durable immune response in most survivors. - Stephanie M LaVergne; Saori Sakabe; Mambu Momoh; Lansana Kanneh; Nell Bond; Robert F Garry; Donald S Grant; Juan Carlos de la Torre; Michael B A Oldstone; John S Schieffelin; Brian M Sullivan (Public Library of Science (PLoS), 2022)
Introduction Lassa virus is a priority pathogen for vaccine research and development, however the duration of cellular immunity and protection in Lassa fever (LF) survivors remains unclear. Methods We investigated Lassa virus specific CD8+ T cell responses in 93 LF survivors. Peripheral blood mononuclear cells from these individuals were infected with recombinant vesicular stomatitis virus encoding Lassa virus antigens and virus specific T cell responses were measured after 18-hour incubation. Participants who had undetectable CD8+ T cell response underwent further analysis using a 10-day T cell proliferation assays to evaluate for low T cell precursor frequency. Results Forty-five of the 93 LF survivors did not have a Lassa virus specific CD8+ T cell response. Of those with responses and a known date of onset of LF (N = 11), 9 had LF within the last ten years. Most participants without a measurable CD8+ T cell response were more than 10 years removed from a clinical history of LF (N = 14/16). Fourteen of 21 patients (67%) with undetectable CD8+ T cell response had a measurable Lassa virus specific CD8+ T cell response with the 10-day assay. Discussion Despite reports of strong CD8+ T cell responses during acute Lassa virus infection, circulating Lassa virus-specific CD8+ T cells declined to undetectable levels in most Lassa fever survivors after ten years when evaluated with an 18-hour T cell stimulation. However, when Lassa virus-specific T cells were expanded prior to restimulation, a Lassa virus-specific CD8+ T cell response could be detected in many if the samples that were negative in the 18-hour stimulation assay, suggesting that prolonged cellular immunity does exist in Lassa fever survivors at low frequencies.